Molecular biology of B cells - e; Reth, Michael; Radbruch, A. (Andreas); Alt, Frederick W. (London : Elsevier Science, 2015)
Molecular Biology of B Cells, Second Edition is a comprehensive reference to how B cells are generated, selected, activated and engaged in antibody production. All of these developmental and stimulatory processes are described in molecular, immunological, and genetic terms to give a clear understanding of complex phenotypes. Molecular Biology of B Cells, Second Edition offers an integrated view of all aspects of B cells to produce a normal immune response as a constant, and the molecular basis of numerous diseases due to B cell abnormality. The new edition continues its success with update.
6. EARLY B CELL FACTOR: CENTRAL COORDINATOR OF B CELL DEVELOPMENT7. COLLABORATION BETWEEN EBF1 AND FOXO1; 8. REGULATION OF THE B CELL-SPECIFIC PROGRAM BY PAX5; 9. REGULATION OF B LINEAGE COMMITMENT; 10. CONCLUSION; ACKNOWLEDGMENT; REFERENCES; Chapter 4 -- Relationships among B Cell Populations Revealed by Global Gene Analysis; 1. INTRODUCTION; 2. GENE PROFILE CHANGES WITH B CELL MATURATION SUGGEST AN ORDERING OF TRANSITIONAL STAGES; 3. DISTINCTIONS IN GENE NETWORKS ACTIVATED IN MATURE B CELL POPULATIONS.
Includes bibliographical references and index.
Online resource; title from PDF title page (ScienceDirect, viewed on November 6, 2014).
Keywords: Molecular immunology; B cells; B cells -- Differentiation -- Molecular aspects; Immunoglobulins; Immunoglobulin genes; B-Lymphocytes.; Immunoglobulins; Cell Differentiation -- physiology; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; B cells; B cells -- Differentiation -- Molecular aspects; Immunoglobulin genes; Immunoglobulins; Molecular immunology; Electronic books